Identifikasi Jenis Kerusakan Pada Perkerasan Lentur (Studi Kasus Jalan Soekarno-Hatta Bandar Lampung) - Putri, Vidya Annisah; Diana, I Wayan; Putra, Sasana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Soekarno-Hatta Bandar Lampung road is a national road which has function as a primary arterialroad. This road having wide 2 x 7,75 m with 4/2 D type of road. This research aims to determineSoekarno-Hatta Bandar Lampung pavement condition. The method used to assessment isPavement Condition Index (PCI). Based on the result of the study, it is known pavement conditionat Soekarno-Hatta Bandar lampung road is excellent 64,3 %; very good 21,4 % and good 14,3 %.Despite the overall condition of the road was still good even perfect category, but at somelocation the road has been damaged. Types of damage that found in this road consisting ofalligator cracking 12,64 %; block cracking 4,66%; bugs 3,35 %; depressions 2,96 %; edgecracking 4,05 %; shoulder drop off 4,14 %; longitudinal cracking 8,81 %; patching 24,61 %;polished aggregate 17,18 %, potholes 3,35 %; rutting 8,76 %; slippage cracking 2,58 % andraveling 2,92 %.Keywords : road damage, pavement condition index